Development of E-Comic Based Learning Media to Increase Student Learning Motivation on Journal Material Adjusted by Service Companies for Class XII High School Students - Nurfitri Ramadana; Ani Widayati (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to develop e-comic-based learning media to enhance the motivation of Grade XII students at SMA Kolombo in learning adjusting journal entries for service companies. The research employed the ADDIE development model with a control group experimental design. Media evaluations indicated that the e-comic is highly feasible, scoring 4.77 from media experts, 3.88 from material experts, and 5.27 from Accounting teachers. Data collected through observations, interviews, and questionnaires showed a significant motivation improvement in the experimental class, with average scores increasing from 90.62 to 105.69, compared to a less significant increase in the control group. An independent t-test confirmed significant differences between the groups (p < 0.05), demonstrating the e-d effectiveness. This study recommends e-comic media as an engaging, interactive, and efficient innovation to improve students' motivation in learning accounting concept..